PETA KETERSERAPAN TENAGA KERJA KREATIF: ANALISIS SPASIAL LULUSAN SMK DKV PADA ZONA KOMERSIAL JAKARTA UTARA - Waruwu, Putri; Nugratama, Sony; Munandar, Aris (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2026)
This study aims to analyze the employment rate of SMK graduates majoring in DKV in the commercial areas of North Jakarta and to map the spatial distribution of graduates' employment locations. With the growth of the creative economy in urban areas, North Jakarta has become a key location due to its numerous active commercial zones. This study employed a quantitative descriptive research method. Data collection was conducted through questionnaires distributed to SMK graduates in North Jakarta. Data analysis was conducted using descriptive statistics to assess employment rates, and NNA with the aid of geographic information system software (ArcGIS) to determine employment distribution patterns. The results of this study indicate that the employment rate of SMK graduates in North Jakarta is quite good. The results of the NNA spatial analysis show of 0.879 and a z-score of -0.161102, indicating that the distribution of graduates' work locations is random. This pattern indicates that employment opportunities for graduates in the creative economy are evenly distributed across all commercial zones in North Jakarta and are not concentrated in any particular industrial cluster. This study concludes that the number of commercial areas in North Jakarta is closely related to opportunities for creative workforce absorption